Blood Pressure Control Education in Hypertension Patients in the Balowerti Community Health Center Area, Kediri City - Mietha Ferdiana Putri; Tartilah Nur Amani; Laras Laxita; Heni Lastari (Universitas STRADA Indonesia, 2025)
The crude death rate in the Balowerti Health Center area in 2020 was 7.28/1000 population, hypertension was the second highest cause of death for the population. From the community service of the Balowerti Health Center Performance Assessment 2023, it was found that the percentage of people with hypertension whose blood pressure was under control only reached 15.6% of the target of 63%. The aim is to provide information or an overall picture regarding strategies for controlling blood pressure so that the target of reducing systolic and diastolic pressure (less than 140/90 mmHg) can be achieved within a period of 1 year. The analysis uses fishbone diagrams to indentify problems, the USG (Urgency, Seriousness, Growth) method to determine problem priorities and SWOT analysis (Strength, Weakness, Opportunity, Threat) to identify strategies in determining intervension plans. Based on the results of the fishbone, USG and SWOT analysis, the implementation strategy that can be implemented is educate patients and the community about the importance of controlling blood pressure, by collaborating with other programs such as Elderly Integrated Service Post, Integrated Coaching Post Non-Communicable Disease, Chronic Disease Management Program.